1989
DOI: 10.1111/j.1365-2141.1989.tb07647.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes in lymphocytes from normal subjects and patients with chronic lymphocytic leukaemia: increased glutathione peroxidase activity in CLL B lymphocytes

Abstract: The activities of several enzymes that protect against oxidative injury were determined in blood lymphocytes from patients with B chronic lymphocytic leukaemia (CLL) and from normal subjects. Similar glutathione reductase (GR), catalase and glucose-6-phosphate dehydrogenase (G6PD) activities were found in normal and CLL lymphocytes. Higher glutathione peroxidase (GP) activity was found in CLL lymphocytes. This activity in CLL B lymphocytes was 2-fold higher than that of normal B lymphocytes, and 3-fold higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
13
1
1
Order By: Relevance
“…Further analyses revealed that the elevated ROS in CLL cells was associated with attenuation of antioxidant capacity, since there was a significant decrease in cellular glutathione (both GSH and GSSG), whereas glutathione peroxidase (GPX) enzyme activity in CLL cells was comparable with that of normal lymphocytes ( Figure 3C,D). Because GSH can be oxidized to GSSG for exportation outside the cells and glutathione reductase activity is similar in CLL and normal lymphocytes, 25 the GSSG/GSH ratios were similar in both cell types ( Figure 3C). Western blot analysis showed an elevation of gamma-glutamyl-cysteine synthetase (GSH1) protein expression in CLL cells ( Figure 3E), suggesting a possible compensatory mechanism of CLL cells in response to ROS stress and increased consumption of glutathione.…”
Section: High Ros and Low Glutathione Are Intrinsic Properties Of Cllmentioning
confidence: 92%
“…Further analyses revealed that the elevated ROS in CLL cells was associated with attenuation of antioxidant capacity, since there was a significant decrease in cellular glutathione (both GSH and GSSG), whereas glutathione peroxidase (GPX) enzyme activity in CLL cells was comparable with that of normal lymphocytes ( Figure 3C,D). Because GSH can be oxidized to GSSG for exportation outside the cells and glutathione reductase activity is similar in CLL and normal lymphocytes, 25 the GSSG/GSH ratios were similar in both cell types ( Figure 3C). Western blot analysis showed an elevation of gamma-glutamyl-cysteine synthetase (GSH1) protein expression in CLL cells ( Figure 3E), suggesting a possible compensatory mechanism of CLL cells in response to ROS stress and increased consumption of glutathione.…”
Section: High Ros and Low Glutathione Are Intrinsic Properties Of Cllmentioning
confidence: 92%
“…Due to prior work demonstrating the vulnerability of CLL B-cells to oxidation [25,[28][29][30], we next evaluated if MSE could rescue CLL B-cells from pharmacologic agents that induce cell death by generating oxidative stress. Glucose oxidase was used as an oxidative challenge in these experiments due to it is ability to generate a pure source of peroxides and induce cell death in CLL B-cells [27,28].…”
Section: Cll Derived Mse Protect Cll B-cells From Spontaneous and Drumentioning
confidence: 99%
“…Ozturk et al (29) observed a significant increase in xanthine oxidase (XO) activity in patients with cancerous human colorectal tissues compared to control group. The increased GSH-Px activities and GSH levels are reported in patients with leukemia (30,31). In our study group, serum ARE was significantly lower than the control group (p <0.001).…”
Section: Resultsmentioning
confidence: 99%